PERILAKU PETANI DALAM PRODUKSI DAN PENANGANAN PANGAN SEGAR DI KABUPATEN LAMPUNG BARAT - Lingga Kusuma; Ahmad Sulaeman; Ikeu Tanziha (Jurnal Gizi dan Pangan, 2008)
The objective of this  research was to analyze farmer’s behavior in the production and post harvest management of fresh food (vegetables). A survey and cross sectional study design were applied in this study. The locations are chosen purposively, ie: Sukarame Village in Balik Bukit Subdistrict and Sekincau Village in Sekincau Subdistrict. The sixty respondents were chosen randomly using stratified sampling method. The data was analyzed descriptively and inferentially. Fresh food farmers in West Lampung District had low knowledge about GAP and also had attitude and behavior that was not appropriate with GAP. Activity in farm group and attitude about GAP had significant correlationship with behavior in production and post harvest management. The farmer’s attitude about GAP has bigger influence on the behavior than the activity in farm group.